Comparative analysis between history and tradition «Pan, queso y raspadura» («Bread, cheese and panela») by Ricardo Palma - Aymerich Lau, Mario (2023)
In this article, the facts narrated in the tradition «Pan, queso y raspadura», by Ricardo Palma, will be compared with the historiographic sources on the battle of Ayacucho. On the one hand, we have the literary value of the story, which highlights the emotional aspects around the events and national heroes of the battle; and, on the other hand, we have the events of history recorded in different historiographic sources. It is not intended to point out the veracity or falsity of the text of the Bibliotecario Mendigo, but to emphasize its importance as an intimate, loyal, and patriotic description of a historical event, such as the battle of Ayacucho.